Mechanisms of mindfulness for professional golfers: the mediating role of basic psychological needs - Chuang, H.-Y.; Wang, F.-J.; Chi, L.-K. (Current Psychology, 2021)
The relationship between mindfulness and well-being and ill-being has been demonstrated to a great extent. In sports, the fulfillment of individuals` basic psychological needs depends mostly on support from others, such as that from a coach in a sports team context. However, a possible way for individuals to fulfill their basic psychological needs is by enhancing mindfulness rather than depending on others. Therefore, building on SDT and mindfulness, this study examines the mediating effect of basic psychological needs on mindfulness to predict subjective vitality and athlete burnout in professional golfers. The participants were 120 golfers (47% females), with a mean age and golf experience of 22.28 and 9.48 years, respectively. The association between mindfulness and subjective vitality was partially mediated by the need for autonomy and relatedness. By contrast, the association between mindfulness and burnout was partially mediated by the need for competence and relatedness, thus supporting our mediation analysis. Overall, the study highlights mindfulness as a potential mechanism to ensure the fulfillment of basic psychological needs in golf training, which could enhance golfers` subjective vitality and reduce the occurrence of burnout.